2004
DOI: 10.1152/japplphysiol.00866.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tidal volume on distribution of ventilation assessed by synchrotron radiation CT in rabbit

Abstract: A respiration-gated synchrotron radiation computed tomography (SRCT) technique, which allows visualization and direct quantification of inhaled stable xenon gas, was used to study the effect of tidal volume (Vt) on regional lung ventilation. High-resolution maps (pixel size 0.35 x 0.35 mm) of local washin time constants (tau) and regional specific ventilation were obtained in five anesthetized, paralyzed, and mechanically ventilated rabbits in upright body position at the fourth, sixth, and eighth dorsal verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 49 publications
2
61
0
Order By: Relevance
“…More recently, similar conclusions were reached using reconstructed images of inhaled fluorescent microsphere content recovered from lung cubes of the order of a cubic centimeter in sheep and pigs (123,124). Using synchrotron radiation computed tomography in rabbits and stable Xe as the inhaled contrast agent, extremely high-resolution images can now be obtained to reveal ventilation distribution of lung units as small as 1.5 mm 3 (125). These more invasive studies are necessarily performed in animal models, and are in support of ventilation heterogeneity potentially occurring at small length scales in various animal species.…”
Section: Inter-and Intraregional Ventilation Heterogeneity Experimentmentioning
confidence: 59%
“…More recently, similar conclusions were reached using reconstructed images of inhaled fluorescent microsphere content recovered from lung cubes of the order of a cubic centimeter in sheep and pigs (123,124). Using synchrotron radiation computed tomography in rabbits and stable Xe as the inhaled contrast agent, extremely high-resolution images can now be obtained to reveal ventilation distribution of lung units as small as 1.5 mm 3 (125). These more invasive studies are necessarily performed in animal models, and are in support of ventilation heterogeneity potentially occurring at small length scales in various animal species.…”
Section: Inter-and Intraregional Ventilation Heterogeneity Experimentmentioning
confidence: 59%
“…9 yields sV ϭ 7.5 min Ϫ1 . The latter value can be compared with sV Ϸ 4.6 min Ϫ1 reported for a rabbit study with VT ϭ 12.7 ml/kg (32).…”
mentioning
confidence: 66%
“…The same process was applied to three different Xe gas image data sets to measure the magnitude of the contrast enhancement. To test the robustness or sensitivity to noise of the time constant with the 30% Xe/30% Kr mixture compared with that with Xe-only studies (30,40, and 55% [Xe]), the mean time constant and the CV* (half 95% CI/mean), obtained by MC simulation, were calculated (see Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation will be needed to verify the measurement of pulmonary regional ventilation using a Xe and Kr mixture in humans. Recent work by Porra et al (30) has shown that dual-energy imaging at either side of the K-edge of Xe gas yields exquisitely detailed images of the gas distribution in the lung. It is of great interest to determine whether dual-energy imaging about the K-edge of Kr may make imaging via Kr alone practical.…”
Section: Comparison Of 30% Xe/30% Kr Mixture With Xementioning
confidence: 99%